(3GdNWH GdYeQjIs - (3CHh GdhLGgI GdeQTOj , YHO GdQMef Hf YjSi Hf eQTO GdYeQj,J (B1037 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd(B: (3deG ef Gddg SHMGfg hJYGdi Ydi ef ShGHZ GdaVd hGdEfYGe HJbdjO efUHj GdEeGeI hGdNWGHI HGdeSLO GdMQGe hPdc aj eaJJM SfI (B1020(3g`, hUQJ CfTF aj cd LeYI NWHI efGSHI ddTgQ GdhGbYI ajg s
(3BNQgG (B:s
(3hYfg Udi Gddg Ydjg hSde Cfg bGd(B: (3Ef aj GdLfI fgQG jbGd dg(B: (3QLH CTO HjGVG ef GddHf hCMdi ef GdYSd s
(3hgj eLehYI NWH CdbGgG Ydi efHQ GdeSLO GdMQGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B164s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B285 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI HGdHUQI (B(138 (3L(B) s
Keywords: (3GdCOHs